Poly[[aqua(μ(2)-oxalato)(μ(2)-2-oxidopyridinium-3-carboxylato)holmium(III)] monohydrate] - Zhu, Hui-Lan (International Union of Crystallography, 2009)
In the title complex, {[Ho(C(2)O(4))(C(6)H(4)NO(3))(H(2)O)]·(H(2)O)}(n), the Ho(III) ion is coordinated by three O atoms from two 2-oxidopyridinium-3-carboxylate ligands, four O atoms from two oxalate ligands and one water molecule in a distorted bicapped trigonal-prismatic geometry. The 2-oxidopyridinium-3-carboxylate and oxalate ligands link the Ho(III) ions into a layer in (100). These layers are further connected by intermolecular O—H⋯O hydrogen bonds involving the coordinated water molecules to assemble a three-dimensional supramolecular network. The uncoordinated water molecule is involved in N—H⋯O and O—H⋯O hydrogen bonds within the layer.